Clinicopathological Correlation Of Glioma Patients With Respect To Immunohistochemistry Markers (International Journal of Environmental Sciences, 2025)
Background: Following the introduction of molecular subtyping in the 2016 WHO classification for gliomas, it has become essential to evaluate the expression patterns of immunohistochemical (IHC) markers in glioma patients and analyze their clinical relevance across different subgroups.Objective: This study aimed to evaluate the IHC marker expression profiles in glioma patients and explore their clinical correlations within various subtypes.Materials and Methods: This retrospective study included 100 patients diagnosed with glioma. IHC staining was performed for markers including isocitrate dehydrogenase 1 (IDH1), ATRX, P53, and Ki‑67. Treatment was administered based on the tumor grade. Patients were followed up every three months over a 12-month period. Data analysis was performed using SPSS software version 20.0, and Microsoft Excel was used to create tables.Results: The majority of patients (52%) were aged 40–60 years, with a slight male predominance (55%). Headache (85%) and seizures (66%) were the most common symptoms, followed by weakness (25%), other symptoms (15%), and altered sensorium (8%). Among 100 tumors graded by WHO, Grade 1 showed no IDH positivity or ATRX loss; Grade 2 had high IDH (76.92%) and moderate ATRX loss (46.15%); Grade 3 showed increased p53 (86.96%) and Ki-67 >5% in 82.61%; Grade 4 had 100% Ki-67 >5% with lower IDH (35%) and ATRX loss (27.5%). Overall, 54% were IDH positive, 34% had ATRX loss, 60% p53 positive, and 69% had Ki-67 >5%. Among histological subtypes, Low-grade tumors like PA and GG showed no IDH positivity or ATRX loss, while DA and AA had moderate to high expression of IDH, ATRX loss, and P53, with increased Ki-67 in AA. P GBM had low IDH and ATRX but high Ki-67 (100%), whereas S GBM showed high IDH, ATRX loss, P53, and Ki-67. ODG had high IDH positivity, moderate P53, and no ATRX loss or Ki-67 elevation, indicating a distinct profile.Conclusion: IHC profiling of gliomas reveals distinct marker patterns across subtypes, aiding in diagnosis and prognostication. IDH positivity and ATRX loss were common in lower grades, while higher grades showed elevated p53 and Ki-67. These markers are valuable tools in aligning histopathology with molecular classification.